Enhancing Consumer Dispute Literacy and The Complaint System of The National Consumer Protection Agency (BPKN) in Realizing A Smart Consumer Society - Subagyono, Bambang Sugeng Ariadi; Anand, Ghansham; Chumaida, Zahry Vandawati (CV Firmos, 2026)
Consumer protection in Indonesia continues to face challenges related to the low level of consumer legal literacy and limited utilization of the complaint mechanisms provided by the National Consumer Protection Agency (BPKN). This study aims to analyze how the improvement of consumer dispute literacy and the optimization of BPKN’s complaint system contribute to the realization of smart consumers in society. Using a juridical-normative approach, this research examines the legal framework governing consumer protection, supported by conceptual and case-based analyses from relevant regulations, legal literature, and official reports. The findings indicate that while Law No. 8 of 1999 on Consumer Protection and Presidential Regulation No. 50 of 2017 provide a solid foundation, the implementation remains hindered by normative limitations, weak institutional coordination, and low legal awareness among consumers. The discussion reveals that the effectiveness of BPKN’s complaint system depends not only on regulatory strength but also on public literacy and participation. Therefore, the study concludes that enhancing consumer literacy and strengthening institutional synergy are crucial in building a responsive and inclusive consumer protection system. These efforts will enable BPKN to play a more strategic role in empowering consumers and fostering a culture of smart, critical, and legally aware consumption behavior.